The Recreational Potential of Green Open Spaces as a Leveraging Factor for Green Economic Development - Delfy Lensari; Noril Milantara; Lulu Yuningsih; Jun Harbi; Rasyid Rasyid (Journal of Global Sustainable Agriculture, 2023)
Kambang Iwak (KI) RTH in Palembang is an oasis for the life of Palembang City. KI Park is always busy with residents visiting for recreation, on weekends KI Park is a place to unwind for local workers, and residents to exercise. The green route of the Muaro River in Padang City nowadays tends to be busy with city residents, especially in the afternoon before Maghrib, and several spots even have non-permanent stalls set up to facilitate residents' activities. These two green open spaces are mini objects in this research to see their recreational potential. This research aims to look at the recreational potential of residents in the Kambang Iwak RTH (Palembang, South Sumatra) and the Muaro River Green Route (Padang, West Sumatra). This research was carried out in two cities in two provinces, namely: 1) Kambang Iwak RTH, Palembang City, South Sumatra Province, and 2) Muaro River Green Belt, Padang City, West Sumatra Province. The data collected in this research was divided into 2 (two) groups, namely primary data and secondary data. The recreational potential in both green open spaces looks at the internal aspects of visitors which are obtained through questionnaires to visitors who are currently using the green open spaces. The research results showed that the highest user choice was the recreational potential of the Kambang Iwak Palembang green open space as a recreational destination for residents were enjoying culinary delights (93.47%), walking (91.84%), enjoying nature (89.39%), enjoying the air (88, 16%), chatting (85.71%), playing (75.92%), studying (66.94%), and cycling (59.59%), while the Sungai Muaro Padang RTH as a recreation destination for residents is to enjoy nature (84.52%), chatting (84.52%), enjoying the air (82.58), enjoying culinary delights (74.84%), traveling (74.19%), studying (74.19%), playing (67.74%), cycling (62.58%), and fishing (62.58%).